2003
DOI: 10.2174/1381612033453910
|View full text |Cite
|
Sign up to set email alerts
|

Cilostazol as a Unique Antithrombotic Agent

Abstract: Cilostazol (CLZ) was originally developed as a selective inhibitor of cyclic nucleotide phosphodiesterase 3 (PDE3). PDE3 inhibition in platelets and vascular smooth muscle cells (VSMC) was expected to provide an antiplatelet effect and vasodilation. Recent preclinical studies have demonstrated that CLZ also possesses the ability to inhibit adenosine uptake by various cells, a property that distinguishes CLZ from other PDE3 inhibitors, such as milrinone. After extensive preclinical and clinical studies, CLZ has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
158
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 166 publications
(161 citation statements)
references
References 0 publications
1
158
0
Order By: Relevance
“…A PDE3 inhibitor, cilostazol, is used as a vasodilating anti-platelet drug for treating intermittent claudication, and in preclinical studies was shown to have a protective effect on endothelial cells by increasing eNOS activity 23) . Cilostazol increases intracellular cAMP content accordingly and activates protein kinase A (PKA) and PI3K/Akt signaling 24) .…”
Section: Cilostazol Inhibits Oxidative Stress-induced Premature Senesmentioning
confidence: 99%
“…A PDE3 inhibitor, cilostazol, is used as a vasodilating anti-platelet drug for treating intermittent claudication, and in preclinical studies was shown to have a protective effect on endothelial cells by increasing eNOS activity 23) . Cilostazol increases intracellular cAMP content accordingly and activates protein kinase A (PKA) and PI3K/Akt signaling 24) .…”
Section: Cilostazol Inhibits Oxidative Stress-induced Premature Senesmentioning
confidence: 99%
“…Therefore, CLZ has been used as a therapeutic agent for the improvement of symptoms in conditions such as cancer (2), pain accompanying chronic arterial obstruction (3), and for the amelioration (4) and, prevention of cerebral infarction (5). The agent is only administered orally because of its low water-solubility (6).…”
Section: Introductionmentioning
confidence: 99%
“…Cilostazol increases intracellular cAMP concentrations by selectively blocking phosphodiesterase 3 (PDE-3), inhibiting platelet aggregation and inducing peripheral vasodilation [14]. Cilostazol is a potent antiplatelet drug used in clinical practice to treat patients with chronic vascular obstruction [15].…”
Section: Introductionmentioning
confidence: 99%